A proposed framework for assessing ecosystem goods and services from planted forests - Baral, H.; Guariguata, Manuel R.; Keenan, R.J. (Elsevier, 2016)
The planting of forests has been met with both scepticism and support in international forest policy and management fora. Discussions regarding the values of plantations for extrinsic purposes such as timber supply, carbon sequestration, water quality and biodiversity conservation, reveal widely varying opinions across and within different settings. Recent research highlights the role of planted forests in providing multiple ecosystem services to human society. However, there has been little assessment of ecosystems services, partly due to lack of suitable frameworks and evaluation tools. Planted forests generally have low ecosystem services values initially and are more vulnerable to erosion and other impacts of mismanagement than natural forests. Careful monitoring of change in ecosystem services values over time is therefore vital to investors and all stakeholders in plantations. Drawing on lessons derived from ecosystem services assessment for various land use types, here we propose an easy-to-apply framework to assess ecosystem services from planted forests that could be used in various planted forest types around the world. A necessary next step for researchers and practitioners is to test the proposed framework under various settings.